Enhancing the Security of Medical Data Using Time Stamp Series - R. , Surya; G. , Charlyn Pushpa Latha (International Journal of Psychosocial Rehabilitation, 2020)
Since blockchain was presented through Bitcoin, research has been continuous to broaden its applications to non-money-related use cases. Human services are one industry in which blockchain is normal to have huge effects. Research right now is moderately new yet developing quickly; in this way, wellbeing informatics analysts and specialists are continually battling to keep up with inquiries about advancement right now. This paper writes about a precise survey of the progressing research in the use of blockchain innovation in medicinal services. The survey shows that various investigations have proposed diverse use cases for the utilization of blockchain in social insurance; be that as it may, there is an absence of satisfactory model usage and studies to portray the viability of these proposed use cases. The survey further features the cutting edge in the advancement of blockchain applications for human services, their constraints, and the regions for future research. To this end, in this way, there is as yet the requirement for more research to all the more likely comprehend, describe, and assess the utility of blockchain in human services.